A Harder and Longer Process? Dispelling Myths about Women in Judicial Primary Elections. (2nd October 2021) - Eugenis, Kate
Abstract: Research suggests that women who run in elections for state supreme court tend to do well in those elections. However, this begs the question: how do those women fare in judicial primary elections and is the subsequent success just a reflection of a more arduous primary process? Using a unique dataset of judicial primary elections from 1990 through 2016, I establish similarities and differences in the structural process and test hypotheses about the paths women take when running for state supreme court. Taking into account the different structural paths available to women, I find women have an advantage in primary elections in that they are more likely to "win" and move to the general elections. However, I also find incumbent women are more likely to attract women as challengers when running in primary elections, and women are more likely to attract challengers in nonpartisan judicial elections. This finding may be mitigated by differences in the primary process based on state. Overall, I find women do not have a disadvantage in the judicial primaries, and often have an advantage over similarly situated men. As a whole, this work paints a nuanced picture of the ways women are elected to state supreme court. These findings also dispel many assumptions about the disadvantages women are thought to have when running for state supreme court.